Real-time teleconsultation with high-resolution and large-volume medical images for collaborative healthcare. - Jianguo Zhang (IEEE Transactions on information technology in biomedicine)
Real-time consultation between referring physicians or radiologists with an expert is critical for timely and adequate management of problem cases. During consultation, both sides need to: 1) synchronously manipulate high-resolution digital radiographic images or large volume MR/CT images; 2) perform interpretation interactively; and 3) converse with audio. We present a specifically designed teleconsultation system in a digital imaging and communication in medicine picture archiving and communication systems (PACS) clinical environment. The system uses bidirectional remote control technology to meet critical teleconsultation application requirements with high-resolution and large-volume medical images operated in a limited bandwidth network setting. We give the system design and implementation methods, and also describe the teleconsultation procedure and protocol used in this system. Finally, laboratory and clinical evaluation results are discussed.